Predicting the long term effects and the risks of abuse and misuse in long term opioid users with chronic non-cancer pain - Zin, Che Suraya (2019)
Little is known about the patterns of analgesic prescribing particularly on opioid prescribing in Malaysia. The issue related to persistence and adherence to opioid therapy is unclear and whether the initial characteristics of opioid prescribing influence the long term use of opioids is also unknown.